Histamine and Delirium: Current Opinion - Chazot, Paul L.; Johnston, Laura; Mcauley, Edel; Bonner, Stephen (Frontiers in Pharmacology, 2019)
Delirium is a very common, but refractory clinical state, notably present in intensive care and in the growing ageing community. It is characterized by fluctuating disturbances in a number of key behavioural features, namely cognition, mood, attention, arousal, and self-awareness. Histamine is arguably the most pleotropic neurotransmitter in the human brain, and this review provides a rationale, and proposes that this neuroactive amine plays a role in modulating the characteristic features of delirium. While centrally-permeable H1 and H2 histamine receptor antagonists have pro-delirium potential, we propose that centrally-permeable H3 histamine receptor antagonists may provide an exciting new strategy to combat delirium. The Histamine H4 receptor may also have an indirect inflammatory neuroglial role which requires further exploration.